2017
DOI: 10.1002/2016jd026422
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study on the electric field spectral dependence of thunderstorm ground enhancements and gamma ray glows

Abstract: We have done a thorough simulation analysis on the variability of the photon spectra produced with (due to Relativistic Runaway Electron Avalanche—RREA) and without (Modification of Spectra) the avalanche multiplication process. Despite some measurements obviously showing a variability of the spectra, numerous theoretical studies consider RREA spectrum independent on the electric field. However, analytical calculations by Cramer et al. (2014) have shown that RREA spectrum under low electric fields is not const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 30 publications
2
18
0
Order By: Relevance
“…This mechanism requires field strength of just a fraction of E t but gives the cosmic background electron and positron sufficient extra energy to produce enhanced fluxes of gamma rays. The spectral shape resulting from RREA and MOS was also investigated by Cramer et al () who found similar spectral behavior as reported by Chilingarian et al ().…”
Section: Introductionsupporting
confidence: 71%
“…This mechanism requires field strength of just a fraction of E t but gives the cosmic background electron and positron sufficient extra energy to produce enhanced fluxes of gamma rays. The spectral shape resulting from RREA and MOS was also investigated by Cramer et al () who found similar spectral behavior as reported by Chilingarian et al ().…”
Section: Introductionsupporting
confidence: 71%
“…The technique could be made more sensitive to E ‖ by adding antennas that are sensitive to the 1 to 10 MHz band (see Trinh et al, ). For moderate‐to‐high E ‖ fields at low altitude above the ground, one would expect a clear increase in the count rate of particle detectors on the ground (see, e.g., Chilingarian et al, ; Cramer et al, ). We have searched for enhanced count rates in the LORA detectors (Wempe, ) but not found any, which is supporting the fact that the fields at low altitude are relatively weak.…”
Section: Cosmic‐ray Tomography Of Cloud Electric Fieldsmentioning
confidence: 99%
“…This value is a standard for modeling RREA process in the large-scale atmospheric electric fields. However, Cramer et al (2017) showed that the accelerated electron spectrum significantly depends on the electric field strength near the RREA threshold, even for homogeneous electric fields. Until recently, there was an opinion that the spectrum of the accelerated electrons in fully developed RREAs should not depend on the electric field, and the electron spectrum can be described by an exponential function with a cutoff at 7.3 MeV (see, e.g., Dwyer & Babich, 2011).…”
Section: Spectral Dependencementioning
confidence: 99%